Intrapartum and neonatal single-dose nevirapine compared with zidovudine for prevention of mother-to-child transmission of HIV-1 in Kampala, Uganda: 18-month follow-up of the HIVNET 012 randomised trial - Jackson, J. Brooks; Musoke, Philippa; Fleming, Thomas; Guay, Laura A.; Bagenda, Danstan; Allen, Melissa; Nakabiito, Clemensia; Sherman, Joseph; Bakaki, Paul; Owor, Maxensia; Ducar, Constance; Deseyve, Martina; et al. (The Lancet, 2003)
In 1999, we reported safety and efficacy data for short-course nevirapine from a Ugandan perinatal HIV-1 prevention trial when 496 babies were followed up to age 14–16 weeks. Safety and efficacy data are now presented for all babies followed up to 18 months of age. Methods From November, 1997, to April, 1999, HIV-1 infected pregnant women in Kampala, Uganda, were randomly assigned nevirapine (200 mg at labour onset and 2 mg/kg for babies within 72 h of birth; regimen A) or zidovudine (600 mg orally at labour onset and 300 mg every 3 h until delivery, and 4 mg/kg orally twice daily for babies for 7 days, regimen B). Infant HIV-1 testing was done at birth, age 6–8 and 14–16 weeks, and age 12 months by HIV-1 RNA PCR, and by HIV-1 antibody at 18 months. HIV-1 transmission and HIV-1-free survival were assessed using Kaplan-Meier analysis. We recorded adverse experiences through 6–8 weeks postpartum for mothers, and 18 months for babies. Efficacy analyses were by intention to treat. Findings We enrolled 645 mothers to the study: 313 were assigned regimen A, 313 regimen B, and 19 placebo. Eight mothers were lost to follow-up before delivery. 99% of babies were breastfed (median duration 9 months). Estimated risks of HIV-1 transmission in the zidovudine and nevirapine groups were 10·3% and 8·1% at birth (p=0·35); 20·0% and 11·8% by age 6–8 weeks (p=0·0063); 22·1% and 13·5% by age 14–16 weeks (p=0·0064); and 25·8% and 15·7% by age 18 months (p=0·0023). Nevirapine was associated with a 41% (95% CI 16–59) reduction in relative risk of transmission through to age 18 months. Both regimens were well-tolerated with few serious side-effects. Interpretation Intrapartum/neonatal nevirapine significantly lowered HIV-1 transmission risk in a breastfeeding population in Uganda compared with a short intrapartum/neonatal zidovudine regimen. The absolute 8·2% reduction in transmission at 6–8 weeks was sustained at age 18 months (10·1% [95% CI 3·5–16·6]). This simple, inexpensive, welltolerated regimen has the potential to significantly decrease HIV-1 perinatal transmission in less-developed countries.
Keywords: Intrapartum; Neonatal single-dose nevirapine; Zidovudine; Mother-to-child transmission of HIV-1; HIVNET 012